An extended gradient-enhanced damage-plasticity model for concrete considering nonlinear creep and failure due to creep. (15th May 2022) - Dummer, Alexander; Neuner, Matthias; Hofstetter, Günter
Abstract: For high stress levels, the dependence of the creep strain rate of concrete on the acting stress is nonlinear. Furthermore, very high stress levels may lead to a critical growth of microcracks resulting in material failure. For the lifetime assessment of creep sensitive concrete structures by means of numerical simulations, the realistic description of nonlinear creep is crucial. However, many concrete models are formulated for either nonlinear time-independent material behavior, or time-dependent material behavior, restricted to linear creep. This is the motivation for extending a damage-plasticity model, aiming at a unified and computationally efficient approach for representing the highly nonlinear time-dependent material behavior of concrete. Well established approaches for modeling the evolution of material properties, inelastic deformation, damage, creep and shrinkage serve as basis for considering nonlinear creep and material failure due to high sustained acting stress. The extended material model for concrete is validated by comprehensive experimental results from the literature. Highlights: Extension of a damage-plasticity model for concrete to nonlinear creep. A novel approach for modeling nonlinear creep and failure due to creep. Application of a gradient-enhanced formulation for mesh-insensitive results. Extensive validation of the proposed model by uniaxial and multiaxial test data. Application to 3D FE simulations of a beam characterized by failure due to creep.